CAR-T Cell Performance: How to Improve Their Persistence? - López-Cantillo, Gina; Urueña, Claudia; Camacho, Bernardo Armando; Ramírez-Segura, Cesar (Frontiers in Immunology, 2022)
Adoptive cell therapy with T cells reprogramed to express chimeric antigen receptors (CAR-T cells) has been highly successful in patients with hematological neoplasms. However, its therapeutic benefits have been limited in the case of solid tumors. Even patients who respond to this immunotherapy remain at risk of relapse due to short-term persistence or no expansion of CAR-T cells; moreover, the hostile tumor microenvironment leads to dysfunction of these cells after reinfusion. Some research has shown that in adoptive T cell therapies, the presence of less differentiated T cell subsets within the infusion product associates with better clinical outcomes. Naïve and memory T cells persist longer and exhibit greater antitumor activity than effector T cells. Therefore, new methods are being studied to overcome the limitations of the therapy to generate CAR-T cells with these ideal phenotypes. Here we review the characteristics of T cell subsets and their implication in the clinical outcome of the adoptive therapy with CAR-T cells; also, we describe some strategies developed to overcome the reduced persistence of CAR T-cells and alternatives to improve this therapy by increasing expansion ability and longevity of modified T cells. These methods include cell culture optimization, incorporating homeostatic cytokines during the expansion phase of manufacturing, modulation of CAR-T cells metabolism, manipulating signaling pathways involved in T cell differentiation, and strategies related to CAR-construct designs.